Spatial and temporal variability of seed bank resulting from overgrowing of xerothermic grassland - Joanna Czarnecka (Acta Societatis Botanicorum Poloniae, 2011)
The aim of my study was to determine changes in the seed bank and vegetation during the process of overgro-wing of the xerothermic grassland situated on the slopes of the White Mountain (349 m a. s. l., the Central Roztocze Region, South-Eastern Poland). I also examined whether the changes of vegetation can be predicted if we know the structure of the burned seed flora. To achieve this goal I used two sets of data: one collected from three different environments (grassland, brushwood and woodland) at the same time (toposequence), and the other collected twice from the same place at the interval of seven years (chronosequence). I stated that the appearance of even a small number of ornitochorous seeds and their seedlings can be treated as a signal that the bush encroachment will accelerate. Seed number seems to decrease during succession in the analysed sequence of plant communities. The total number of species in the seed bank did not change in the most dynamic plant communities: grassland and brushwood, and it was significantly higher there than in the seed bank of woodland. During the time of observation, the most important quantitative and qualitative changes took place in grassland vegetation, which is more similar to brushwood vegetation now than it was at the beginning of the study.